Diseño y construcción de un banco hidráulico para prueba de caudales aplicado a la acuacultura - Márquez Pizarro, Carlos Alberto (2015)
Hydropower is the part of physics, studying fluid mechanics. Their study is possible to analyze the laws governing the motion of liquids and techniques for better utilization of the waters. Also, by mathematical calculation, the design of small-scale models and experiment with them, you can determine the design characteristics that must have dams, harbors and canals. The laboratories play an important role in higher education as a place for students to apply theoretical knowledge to real situations. However, these are quite modest and only allow the implementation of very basic devices. In this sense, theoretical programs can be used to complement the practical hydraulic and apply in practice the concepts. Hydraulic bench was constructed and installed in laboratory bioassays Ecology and Aquaculture Race Engineering. The hydraulic bench consists of a storage tank and a provisional pre-alignment system that allows appraisals to determine the flow through the spillway according to your figure to the tank outlet. It is considered necessary to have this type of equipment, under which they can achieve the objectives for academic programs and similarly students career aquaculture engineering can link theory with practice, for it was built a hydraulic bench which allows support the teachers and students to measure spending, flow and speed of flow through the gates (landfill). With hydraulics bench is to provide fundamental knowledge in the laboratory in the formation of farmer Engineer.